Electrophoretic Mobility of Cell Nuclei (EMN) index — relation to biological and physical properties of the cell - Czapla, Zbigniew; Cieślik, Joachim (Polskie Towarzystwo Antropologiczne, 1998)
The authors describe certain physical and biological properties of cell and resulting electrical and electrokinetic properties, directly or indirectly related with the Electrophoretic Mobility of Cell Nuclei (EMN) index. This index, may become a new criterion in the estimation of the biological age, irrespective of the stage of the ontogenesis.